M2S and CAIR. Image based information retrieval in mobile environments. - Aarbakke, Anne Staurland (Universitetet i Tromsø, 2007)
Images are commonly used on a daily basis for research, information and entertainment. The introduction of digital cameras and especially the incorporation of cameras in mobile phones makes people able to snap photos almost everywhere at any time since their mobile phone is almost always brought with them. The fast evolution in hardware enables users to store large image collection without high costs. Making use of these image collections requires efficient image retrieval techniques. Traditional image retrieval techniques like text-based image retrieval and content-based image retrieval techniques have shortcomings. New techniques or combination of existing techniques must be established to provide users with adequate image retrieval functionality. This thesis describes two systems enabling users to retrieve information such as images, textual information, WAP-links or videos using SMS or MMS. One of the services, M2S is meant for tourists to retrieve information about attractions in Lofoten. M2S uses content-based image retrieval to retrieve the information requested. This service is designed and implemented in cooperation with Telenor R&I. The other system, CAIR is meant for users who want to retrieve images from an image collection using SMS. CAIR uses a context-based image retrieval to retrieve images. This system is designed, but not yet implemented.